The Shadows - North, Alex, 1976- (New York : Celadon Books, 2020)
"You knew a teenager like Charlie Crabtree. A dark imagination, a sinister smile--always on the outside of the group. Some part of you suspected he might be capable of doing something awful. Twenty-five years ago, Crabtree did just that, committing a murder so shocking that it's attracted that strange kind of infamy that only exists on the darkest corners of the internet--and inspired more than one copycat. Paul Adams remembers the case all too well: Crabtree--and his victim--were Paul's friends."--
Keywords: Murder -- Fiction; Teenage boys -- Fiction; Mothers and sons -- Fiction; Friendship -- Fiction; Murder -- Investigation -- Fiction; Thrillers (Fiction); Horror fiction